Pendampingan Pembuatan Akun Lazada E-Commerce UMKM Garam Rebus di Desa Kaliwlingi - Mohamad Badrun Zaman; Amelia Sholeha; Hendri Sucipto; Siti Nur Aisyah (Institut Teknologi dan Bisnis Semarang, 2024)
In Kaliwlingi Village there are various kinds of MSMEs, such as boiled salt, mangrove batik, soft shell crab, these are all the leading MSMEs in Kaliwlingi Village. Boiled salt is one of the products of Kaliwlingi MSMEs which is a leading MSME. However, Kaliwlingi boiled salt MSMEs also experience several obstacles in running their business, including product marketing which is still by word of mouth, limited human resources and minimal consumer capabilities. The aim of this KKN is to assist in marketing boiled salt products to further expand the boiled salt marketing network. This KKN includes marketing training using E-Commerce and assistance in using E-Commerce. The results of the KKN can be concluded that boiled salt MSMEs in Kaliwlingi Village can run their business professionally, and can increase production capacity due to the increase in the number of customers. The trend regarding the use of E-Commerce in Indonesia will continue to grow and now many people are starting to be selective about E-Commerce because there is intense competition between E-Commerce. What differentiates a company from its competitors lies in the strength of the market itself and UNCTAD (United Nations Conference Trade & Development) has issued a theory of 5 pillars of digital economic strength, namely market share, search engines, social media, video sharing and payment systems. LAZADA Group is a Southeast Asian E-Commerce company founded by rocket internet in 2012, and owned by Alibaba Group. Lazada in Indonesia itself was founded in 2012 and operates until now. Lazada's goal is to be a trusted online shopping place and provide the best quality in terms of quality and service.